No use of any identities

Algebra Level 5

Let α , β \alpha,\beta be the roots of the equation x 2 x 1 = 0 x^2-x-1=0 .

Let a 2 n = α 2 n + β 2 n a_{2n}={\alpha}^{2n}+{\beta}^{2n} where n 1 n\geq1 and n n is a natural number.

What is the value of a 20 + a 22 a_{20}+a_{22} ?


The answer is 54730.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mathh Mathh
Jul 5, 2015

By Vieta's formulas a 1 = 1 a_1=1 , by Newton's sums a 2 a 1 2 = 0 a_2-a_1-2=0 , i.e. a 2 = 3 a_2=3 .

By Newton's sums : a k = a k 1 + a k 2 a_k=a_{k-1}+a_{k-2} for k 3 k\ge 3 .

With this recurrence relation find a 20 , a 22 a_{20},a_{22} .

In fact, since a 0 = 2 a_0=2 , we have a k = L k a_k=L_k for all k 0 k\ge 0 , where ( L n ) n 0 (L_n)_{n\ge 0} is the sequence of Lucas numbers . So you can just see a list of those numbers, e.g. here .


Alternatively (more elementary):

By Vieta's formulas a 1 = 1 , α β = 1 a_1=1, \alpha\beta=-1 .

a 2 = a 1 2 2 α β = 3 a_2=a_1^2-2\alpha\beta=3 .

a k = a k 1 a 1 α β a k 2 a_k=a_{k-1}a_1-\alpha\beta a_{k-2} , i.e.

a k = a k 1 + a k 2 a_k=a_{k-1}+a_{k-2} .


Another way:

a 4 = a 2 2 2 α 2 β 2 a_4=a_2^2-2\alpha^2\beta^2

a 8 = a 4 2 2 α 4 β 4 a_8=a_4^2-2\alpha^4\beta^4

a 16 = a 8 2 2 α 8 β 8 a_{16}=a_8^2-2\alpha^8\beta^8

a 20 = a 16 a 4 α 4 β 4 ( a 8 a 4 α 4 β 4 a 4 ) a_{20}=a_{16}a_{4}-\alpha^4\beta^4(a_8a_4-\alpha^4\beta^4a_4)

a 22 = a 20 a 2 α 2 β 2 ( a 16 a 2 α 2 β 2 ( a 8 ( a 4 a 2 α 2 β 2 a 2 ) α 6 β 6 a 2 ) ) a_{22}=a_{20}a_2-\alpha^2\beta^2(a_{16}a_2-\alpha^2\beta^2(a_8(a_4a_2-\alpha^2\beta^2a_2)-\alpha^6\beta^6a_2))

Or a 22 = a 16 ( a 4 a 2 α 2 β 2 a 2 ) α 6 β 6 ( a 8 a 2 α 2 β 2 ( a 4 a 2 α 2 β 2 a 2 ) ) a_{22}=a_{16}(a_4a_2-\alpha^2\beta^2a_2)-\alpha^6\beta^6(a_8a_2-\alpha^2\beta^2(a_4a_2-\alpha^2\beta^2a_2))

Moderator note:

Good eye for spotting Lucas Numbers!

Excellent You have a good knowledge

Shubham Garg - 5 years, 11 months ago
Shubham Garg
Jul 5, 2015

The equation is x 2 x 1 = 0 x^2-x-1=0

Since β \beta is a root,

β 2 β 1 = 0 {\beta}^2-{\beta}-1=0 .

Multiplying both sides by β 2 n + 2 {\beta}^{2n+2}

β 2 n + 4 β 2 n + 3 β 2 n + 2 = 0 \Rightarrow {\beta}^{2n+4}-{\beta}^{2n+3}-{\beta}^{2n+2}=0 ................................. ( i ) (i)

and multiplying both sides by β 2 n + 1 {\beta}^{2n+1}

β 2 n + 3 β 2 n + 2 β 2 n + 1 = 0 \Rightarrow {\beta}^{2n+3}-{\beta}^{2n+2}-{\beta}^{2n+1}=0 ................................. ( i i ) (ii)

and multiplying both sides by β 2 n {\beta}^{2n}

β 2 n + 2 β 2 n + 1 β 2 n = 0 \Rightarrow {\beta}^{2n+2}-{\beta}^{2n+1}-{\beta}^{2n}=0 ................................. ( i i i ) (iii)

Now ( i ) + ( i i ) ( i i i ) (i)+(ii)-(iii) we get;

β 2 n + 4 3 β 2 n + 2 + β 2 n = 0 {\beta}^{2n+4}-3{\beta}^{2n+2}+{\beta}^{2n}=0 ............................. ( i v ) (iv)

Similarly;

α 2 n + 4 3 α 2 n + 2 + α 2 n = 0 {\alpha}^{2n+4}-3{\alpha}^{2n+2}+{\alpha}^{2n}=0 ......................... ( v ) (v)

Now ( i v ) + ( v ) (iv)+(v)

( β 2 n + 4 + α 2 n + 4 ) 3 ( β 2 n + 2 + α 2 n + 2 ) + ( β 2 n + α 2 n ) = 0 ({\beta}^{2n+4}+{\alpha}^{2n+4})-3({\beta}^{2n+2}+{\alpha}^{2n+2})+({\beta}^{2n}+{\alpha}^{2n})=0 .

a 2 n + 4 3 a 2 n + 2 + a 2 n = 0 \Rightarrow a_{2n+4}-3a_{2n+2}+a_{2n}=0 .

a 2 = α 2 + β 2 = ( α + β ) 2 2 α β = 1 + 2 = 3 a_{2}={\alpha}^2+{\beta}^2=({\alpha}+{\beta})^2-2{\alpha}{\beta}=1+2=3

a 4 = α 4 + β 4 = ( α 2 + β 2 ) 2 2 α 2 β 2 = 9 2 = 7 a_{4}={\alpha}^4+{\beta}^4=({\alpha}^2+{\beta}^2)^2-2{{\alpha}^2}{{\beta}^2}=9-2=7 .

Now using the recurrence relation derived we can easily calculate

a 20 = 15127 a 22 = 39603 a_{20}=15127 \quad a_{22}=39603

a 20 + a 22 = 54730 \Rightarrow a_{20}+a_{22}=\boxed{54730}

(there is another way of deriving the recurrence relation that is by forming a quadratic equation with roots as α 2 , β 2 ) {\alpha}^2,{\beta}^2) .

to find the equation with α 2 , β 2 {\alpha}^2,{\beta}^2 as roots put x \sqrt{x} in place of x x

The equation becomes

x x 1 = 0 x-\sqrt{x}-1=0

x 1 = x x-1=\sqrt{x}

Squaring

x 2 3 x + 1 = 0 x^2-3x+1=0

now α 2 {\alpha}^2 satisfies this equation

α 4 3 α 2 + 1 = 0 \Rightarrow {\alpha}^4-3{\alpha}^2+1=0

Multiplying by α 2 n {\alpha}^{2n}

α 2 n + 4 3 α 2 n + 2 + α 2 n = 0 {\alpha}^{2n+4}-3{\alpha}^{2n+2}+{\alpha}^{2n}=0

Now similar as above)

Can you show the other method too @shubham garg ? ? ? ? ????

Seeku hhh - 5 years, 11 months ago

Log in to reply

i have edited my solution have a look

Shubham Garg - 5 years, 11 months ago

Log in to reply

Kya baat hai

Rajat Raj - 5 years, 11 months ago

good problem!

Raven Herd - 5 years, 11 months ago

Just thought I'd point out that Phi - the Golden Ratio - is one of the roots of this formula.

Terry Smith - 5 years, 11 months ago

Log in to reply

Golden ratio have many properties

Ram Sita - 3 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...